Effects of Verb Familiarity on Finiteness Marking in Children With Specific Language Impairment - Abel, Alyson D. (J Speech Lang Hear Res, 2015)
PURPOSE: Children with specific language impairment (SLI) have known deficits in the verb lexicon and finiteness marking. This study investigated a potential relationship between these 2 variables in children with SLI and 2 control groups considering predictions from 2 different theoretical perspectives, morphosyntactic versus morphophonological. METHOD: Children with SLI, age-equivalent, and language-equivalent (LE) control children (n = 59) completed an experimental sentence imitation task that generated estimates of children's finiteness accuracy under 2 levels of verb familiarity—familiar real verbs versus unfamiliar real verbs—in clausal sites marked for finiteness. Imitations were coded and analyzed for overall accuracy as well as finiteness marking and verb root imitation accuracy. RESULTS: Statistical comparisons revealed that children with SLI did not differ from LE children and were less accurate than age-equivalent children on all dependent variables: overall imitation, finiteness marking imitation, and verb root imitation accuracy. A significant Group × Condition interaction for finiteness marking revealed lower levels of accuracy on unfamiliar verbs for the SLI and LE groups only. CONCLUSIONS: Findings indicate a relationship between verb familiarity and finiteness marking in children with SLI and younger controls and help clarify the roles of morphosyntax, verb lexicon, and morphophonology.